2017
DOI: 10.1038/s41598-017-15316-6
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Patients with Severe Aortic Stenosis: An Observational study

Abstract: Whether patients with severe aortic stenosis (AS) die because of AS-related causes is an important issue for the management of these patients. We used data from CURRENT AS registry, a Japanese multicenter registry, to assess the causes of death in severe AS patients and to identify the factors associated with non-cardiac mortality. We enrolled 3815 consecutive patients with a median follow-up of 1176 days; the 1449 overall deaths comprised 802 (55.3%) from cardiac and 647 (44.7%) from non-cardiac causes. Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 24 publications
2
24
1
Order By: Relevance
“…Furthermore, sympathetic over-activity, typical in chronic heart failure, could also play an important role as malignant ventricular arrhythmias’ trigger. In such a context, there are two previous observations corroborating these claims: it was recently confirmed that the sudden cardiac death during AS remains statistically important (Minamino-Muta et al, 2017) and, some non-invasive electrocardiographic (ECG) markers were found significantly associated to a poor outcome in elderly patients with AS after the transcatheter aortic valve replacement (TAVR) (Piccirillo et al, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, sympathetic over-activity, typical in chronic heart failure, could also play an important role as malignant ventricular arrhythmias’ trigger. In such a context, there are two previous observations corroborating these claims: it was recently confirmed that the sudden cardiac death during AS remains statistically important (Minamino-Muta et al, 2017) and, some non-invasive electrocardiographic (ECG) markers were found significantly associated to a poor outcome in elderly patients with AS after the transcatheter aortic valve replacement (TAVR) (Piccirillo et al, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…In our study, we provided the link between LV geometric patterns and AF prevalence through the contribution of atrial enlargement and decreased LVEF. AF and LA enlargement is a risk factor for ischemic stroke and may contribute to doubling all-cause 31 and CV deaths 14 , and, in a specific condition, non-CV deaths 32 . However, anticoagulants were sub-optimally prescribed in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic data captured in routine clinical care has been leveraged to populate patient registries and perform retrospective observational studies, including studies that have informed the outcomes of patients with asymptomatic severe AS6 and causes of death among patients with severe AS 7. These prior studies have applied guideline recommended quantitative echocardiographic measures, including valve area, in the identification of patients with severe AS.…”
Section: Discussionmentioning
confidence: 99%